Trend in Improving Teacher Competence in Innovative Learning at Primary School - Tamsik Udin; Sehan Rifky Arfanaldy (Al Ibtida: Jurnal Pendidikan Guru MI, 2025)
Abstract This study aims to identify global trends in improving elementary school teacher competency through innovative learning approaches. The method employed is a systematic literature review (SLR) based on the PRISMA protocol, which analyzes 35 selected articles from reputable international journals published between 2015 and 2024. The results of the study indicate that project-based learning (PBL) is the most dominant approach used in teacher competency development, followed by technology integration and continuous professional training. This study also highlights the importance of techno-pedagogical competency, reflective ability, and adaptation to local socio-cultural contexts. In addition, geographical disparities and access to training were found to have an impact on the education quality gap between regions. This study recommends integrating the TPACK model and reflective practices into teacher training designs, along with contextual and data-driven policies. These findings offer both conceptual and practical contributions to designing strategies that enhance elementary teacher professionalism, aligning with the demands of the 21st century.Keywords: innovative learning, primary education, professional development, teacher competence.AbstrakPenelitian ini bertujuan untuk mengidentifikasi tren global dalam meningkatkan kompetensi guru sekolah dasar melalui pendekatan pembelajaran yang inovatif. Metode yang digunakan adalah tinjauan pustaka sistematis (SLR) berdasarkan protokol PRISMA, yang menganalisis 35 artikel terpilih dari jurnal internasional terkemuka yang diterbitkan antara tahun 2015 dan 2024. Hasil studi menunjukkan bahwa pembelajaran berbasis proyek (PBL) adalah pendekatan yang paling dominan digunakan dalam pengembangan kompetensi guru, diikuti oleh integrasi teknologi dan pelatihan profesional berkelanjutan. Penelitian ini juga menyoroti pentingnya kompetensi tekno-pedagogis, kemampuan reflektif, dan adaptasi terhadap konteks sosial budaya setempat. Selain itu, disparitas geografis dan akses ke pelatihan ditemukan berdampak pada kesenjangan kualitas pendidikan antar-wilayah. Penelitian ini merekomendasikan pengintegrasian model TPACK dan praktik reflektif ke dalam desain pelatihan guru, bersama dengan kebijakan kontekstual dan berbasis data. Temuan ini menawarkan kontribusi konseptual dan praktis untuk merancang strategi yang meningkatkan profesionalisme guru sekolah dasar, yang sejalan dengan tuntutan abad ke-21.Kata kunci: kompetensi guru, pembelajaran inovatif, pendidikan dasar, pengembangan profesional.